Highly reliable access algorithm for PD-NOMA based IoT with delay guarantee - Chaonong XU; Jianxiong WU; Yongjun XU (Tongxin xuebao)
A single-hop PD-NOMA network supporting k-successive interference cancellation (k-SIC) was considered.Given the real-time performance requirements,how to maximize the average reliability of uplink transmissions by the joint users grouping and power allocation was studied.A heuristic algorithm with complexity of O(nlogn) was presented,where n was the number of users.The algorithm was also proved to be the optimal if k=2.The performance evaluations reveal that the transmission reliability will increase exponentially with the linear degradation of the real-time performance guarantee.Besides,the transmission reliability is enhanced with respect to the random users grouping algorithm.